Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1152/ajprenal.00394.2003
|View full text |Cite
|
Sign up to set email alerts
|

Response of descending vasa recta to luminal pressure

Abstract: Zhang, Zhong, and Thomas L. Pallone. Response of descending vasa recta to luminal pressure. Am J Physiol Renal Physiol 287: F535-F542, 2004. First published May 4, 2004 10.1152/ajprenal. 00394.2003.-We tested whether luminal perfusion and pressurization induce an endothelial cytoplasmic Ca 2ϩ ([Ca 2ϩ ]CYT) response in descending vasa recta (DVR). DVR isolated from the rat outer medulla were cannulated and subjected to free-flow microperfusion (5 nl/min); the onset of which increased [Ca 2ϩ ]CYT from a basel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 46 publications
1
22
0
Order By: Relevance
“…Notably, the reaction of NO with hemoglobin is orders of magnitude faster than its consumption by O 2 Ϫ . Moreover, endothelial shearmediated increases in the basal rate of NO production could be a significant variable (58).…”
Section: Mechanisms Underlying H 2 O 2 -Induced Vasoconstrictionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the reaction of NO with hemoglobin is orders of magnitude faster than its consumption by O 2 Ϫ . Moreover, endothelial shearmediated increases in the basal rate of NO production could be a significant variable (58).…”
Section: Mechanisms Underlying H 2 O 2 -Induced Vasoconstrictionmentioning
confidence: 99%
“…Cao and colleagues (4) observed that blockade of NO generation led to substantial vasoconstriction that was partly reversed by scavenging O 2 Ϫ or inhibiting O 2 Ϫ generation. Those experiments were performed under conditions of luminal shear stimulation, i.e., during isolated vessel microperfusion, which markedly enhances endothelial NO generation (58). Other studies in explanted tissue preparations, in which DVR were not perfused, have elegantly shown that NO and O 2 Ϫ from adjacent epithelia can reach DVR pericytes to modify pericyte cytoplasmic Ca 2ϩ levels (10).…”
Section: Mechanisms Underlying H 2 O 2 -Induced Vasoconstrictionmentioning
confidence: 99%
“…When L-NAME (10 Ϫ4 mol/L) was used, it was exchanged into the bath at the same time as the perfusate was exchanged. Perfusion was then restarted, providing flow as a stimulus to DVR endothelial production of NO (22). DAF-FM fluorescence images were captured at 30-second intervals throughout the 20-minute perfusion period.…”
Section: Protocolsmentioning
confidence: 99%
“…NOS 1 29 and NOS 3 30 have been thought to be regulated primarily by increases in intracellular calcium and NOS 2 by changes in expression of the enzyme. 31 However, these views have recently been challenged by studies in a number of renal and other cell types.…”
Section: Regulation Of Nos Activitymentioning
confidence: 99%
“…It is unclear whether this is also true for renal vessels, because flowinduced activation of NOS 3 in the vasa recta does not appear to be caused by phosphorylation at serine 1179, but rather simply an increase in intracellular calcium. 30 In addition to serine 1179, at least 4 other phosphorylation sites on NOS 3 are known. 59 Insulin has also been suggested to enhance NOS 3 activity in the renal medulla by dephosphorylating threonine 495 in diabetic rats.…”
Section: Regulation Of Nos Activitymentioning
confidence: 99%